RELATIONSHIP OF STRESS LEVELS WITH DISORDERS OF MENSTRUATION CYCLE IN STUDENTS - Johari, Dewi Talia; Melani, Linda; Herdiyani, Puspitasari; Sucianny, Wulan Ayu; Fujianti, Ishe; Triwahyuningsih, Ria Yulianti; Kumalasari, Diyanah; Wahyuningsih, Tri (Krafon Publishing, 2019)
Menstrual disorders are quite a lot of problems faced by women with prenatal 75% in late adolescents. One of the causes of menstrual disorders in women is a stress factor. Stress can affect the menstrual cycle, which involves the hormonal system as a system that plays a major role in female reproduction. This study aims to determine the relationship between stress levels and impaired menstrual cycles in students. This study was an observational study with a cross sectional approach. The population in this study were all students of Level I and II of the DIII Midwifery Study Program at the Muhammadiyah Cirebon STIKes 2017/2018 Academic Year totaling 137 female students. Sampling uses probability simple random sampling of 102 people. The instrument for collecting data uses the Modified DASS 42 questionnaire and checklist about the menstrual cycle. Data analysis techniques used the chi-square statistical test and contingency test. The results showed that most (47%) female students experienced very heavy stress and 102 menstrual cycle disorders. The results of the statistical test obtained a significant level of 0.1559 and the size of the contingency coefficient C 0.28. It can be concluded that there is no correlation between stress levels and menstrual cycle disorders with a significant level of 0.1559 and contingency coefficient C 0.28.